P-098 Serious Infections in Patients Treated with Certolizumab Pegol with or Without Corticosteroids: Pooled Safety Data from 15 Clinical Trials. (March 2016) - Abraham, Bincy; Wolf, Doug; Regueiro, Miguel; Randall, Charles; Kosutic, Gordana; Spearman, Marshall; Coarse, Jason; Hasan, Iram; Loftus, Edward
Abstract : Background: Corticosteroid therapy as a treatment for Crohn's disease (CD) is a known risk factor for serious complications. 1 This analysis of pooled safety data from 15 clinical trials examined the possible association between serious infections and the use of corticosteroids in patients with CD treated with certolizumab pegol (CZP; a pegylated, Fc-free antitumor necrosis factor agent). Methods: Safety data from 15 phase 2 or 3 placebo (PBO)-controlled, non-PBO–controlled, or open-label CZP studies were pooled for analysis. In the PBO-controlled studies, 919 patients received CZP and 875 patients received PBO (short-term; studies' duration, 6–36 weeks). In the All Studies CZP group, all 2570 patients who received CZP (long-term; studies' duration, 6–364 weeks) were examined. Patients in the PBO-controlled studies (CZP and PBO treatments) and in the All Studies CZP group were stratified by corticosteroid use at baseline (with corticosteroids or without corticosteroids). The frequency and incidence rate (IR; new events per 100 patient-years) of serious infections were calculated. Results: In the short-term PBO-controlled studies, 228 patients were treated with CZP with corticosteroids, 691 were treated with CZP without corticosteroids, 226 were treated with PBO with corticosteroids, and 649 were treated with PBO without corticosteroids. In these studies, serious infections occurred at the highest frequency in patients treated with CZP with corticosteroids (7 [3.1%]; IR, 10.35 [95% confidence interval (CI), 4.16–21.32]/100 patient-years), followed by CZP without corticosteroids (18 [2.6%]; IR, 7.93 [95% CI, 4.70–12.54]/100 patient-years), PBO with corticosteroids (4 [1.8%]; IR, 6.60 [95% CI, 1.80–16.89]/100 patient-years), and PBO without corticosteroids (10 [1.5%]; IR, 5.05 [95% CI, 2.42–9.29]/100 patient-years). In the longer-term, CZP All Studies group, 636 patients were treated with CZP with corticosteroids and 1934 were treated with CZP without corticosteroids. New events of serious infections occurred more frequently in patients treated with CZP with corticosteroids (92 [14.5%]; IR, 7.73 [95% CI, 6.23–9.48]/100 patient-years) than in those treated with CZP without corticosteroids (176 [9.1%]; IR, 5.96 [95% CI, 5.12–6.91]/100 patient-years). Conclusions: These data demonstrate that the IR of serious infections is higher in patients treated with combination therapy of CZP with corticosteroids relative to PBO with corticosteroids. The IR of serious infections for CZP without corticosteroids falls within the CI of the IR for CZP with corticosteroids. The IR for CZP with and without corticosteroids does not increase with longer-term exposure to CZP. In addition, in the longer-term All Studies CZP group, the IR of serious infections between patients treated with corticosteroids was higher than without corticosteroids. These results suggest that CZP does not have a cumulative effect with regards to serious infections.